2014
DOI: 10.1007/978-3-319-08404-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Covering Problems in Edge- and Node-Weighted Graphs

Abstract: This paper discusses the graph covering problem in which a set of edges in an edge-and nodeweighted graph is chosen to satisfy some covering constraints while minimizing the sum of the weights. In this problem, because of the large integrality gap of a natural linear programming (LP) relaxation, LP rounding algorithms based on the relaxation yield poor performance. Here we propose a stronger LP relaxation for the graph covering problem. The proposed relaxation is applied to designing primal-dual algorithms for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Let us mention that the idea on formulating our LP relaxation is potentially useful for other covering problems. The author pointed out in his recent work [6] that a natural LP relaxation has a large integrality gap for many covering problems in node-weighted graphs. He also presented several tight approximation algorithms using the LP relaxations designed based on the idea we propose in the present paper.…”
Section: Lp Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us mention that the idea on formulating our LP relaxation is potentially useful for other covering problems. The author pointed out in his recent work [6] that a natural LP relaxation has a large integrality gap for many covering problems in node-weighted graphs. He also presented several tight approximation algorithms using the LP relaxations designed based on the idea we propose in the present paper.…”
Section: Lp Relaxationmentioning
confidence: 99%
“…Note: In [6], the author applied a similar idea of lifting LP relaxations for solving several covering problems in edge-and node-weighted graphs. He defined a new LP relaxation by replacing edge variables by variables corresponding to pairs of edges and constraints, and showed that the new LP relaxation has better integrality gap than the original one.…”
Section: Lp Relaxation For Prize-collecting Augmentation Problemmentioning
confidence: 99%
“…In 2008, PAREKH [11] presented an approximate algorithm to solve the prize-collecting edge dominating set problem (PCEDS) problem, algorithm approximate ratio is 8 / 3. In 2010, KAMIYAMA [12] proposed polynomial time algorithm for solving PCEDS problem on edge-weighted tree graphs, and time complexity is 2 ( ) O V ; in 2016, FUKUNAGA [13] promoted the conclusion of KAMIYAMA, in the problem of PCEDS, considering the simultaneous weighting of vertexes and edges on the tree graph, a polynomial time algorithm with time complexity (log ) O V was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous investigations of the interaction topology have focused on edge-weighted graphs, and node weights have been largely neglected. In [31], an algorithmic technique was proposed to deal with the graph covering problem in nodeweighted graphs.…”
Section: Introductionmentioning
confidence: 99%